Bicarbonate modulates delafloxacin activity against MDR Staphylococcus aureus and Pseudomonas aeruginosa. (10th December 2021) - Holland, Mische; Bjanes, Elisabet; Nizet, Victor; Dillon, Nicholas
Abstract: Objectives: To investigate the utility of recently approved delafloxacin and other fluoroquinolones against leading MDR bacterial pathogens under physiologically relevant conditions. Methods: MIC and MBC assays were conducted for MDR strains of Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae in the standard antibiotic susceptibility testing medium CAMHB, amended Roswell-Park Memorial Institute tissue culture medium (RPMI+) or 20% fresh human whole blood. In vivo correlation of in vitro findings was performed in a murine P. aeruginosa pneumonia model. Mechanistic bases for the findings were explored by altering media conditions and with established fluoroquinolone accumulation assays. Results: Fluoroquinolone MICs were increased in RPMI+ compared with CAMHB for all four MDR pathogens. Specifically, delafloxacin MICs were increased 32-fold versus MDR S. aureus and 8-fold versus MDR P. aeruginosa . MBC assays in 20% human whole blood and a murine MDR P. aeruginosa pneumonia model both confirmed that delafloxacin activity was reduced under physiological conditions. Bicarbonate (HCO3 − ), a key component of host physiology found in RPMI+ but absent from CAMHB, dictated delafloxacin susceptibility in CAMHB and RPMI+ by impairing its intracellular accumulation. Conclusions: Standard in vitro antibiotic susceptibility testing conditions overpredicted the effectiveness of delafloxacin against MDR pathogens by failing to capture the role of the biological buffer HCO3 − to impair delafloxacin accumulation. This work showcases limitations of our current antibiotic susceptibility testing paradigm and highlights the importance of understanding host microenvironmental conditions that impact true clinical efficacy.